The regular gymnastics program on the quality of life for elderly people with hypertension - Almaini Almaini; Titin Sumarni; Mulyadi Mulyadi; Fatimah Khoirini (Malahayati International Journal of Nursing and Health Science, 2023)
Background: The quality of life of the elderly may determine their well-being for the remainder of their lives. According to The World Health Organization Quality of Life (WHOQOL), quality of life is an elderly functional condition that encompasses physical health, namely daily activities. One of the primary health problems in the elderly is hypertension. The conventional management of hypertension may be carried out with pharmacological and non-pharmacological therapies. Non-pharmacological methods include improving lifestyle, one of which is by starting physical exercise regularly such as gymnastics for the elderly.Purpose: To determine the relationship the regular gymnastics program on the quality of life for elderly people with hypertensionMethod: Using the cross-sectional research method, the samples were taken randomly from the elderly population domiciled in the area of the East Curup Public Health Center totaling 87 elderly people who met our inclusion and exclusion criteria. The inclusion criteria were men and women aged ≥60 years and the elderly with hypertension based on the diagnosis established by the officials of the public health center. While the exclusion criterion was elderly in emergency situations.Results: The mean systolic and diastolic blood pressure of respondents who gymnastics was lower than those who did not gymnastics.Conclusion: Elderly gymnastics is associated with lower systolic and diastolic blood pressure of the elderly with hypertension, even though it is still higher than the target of hypertension management, and their quality of life.